2019
DOI: 10.1017/s0022215119000392
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of Voice Handicap Index in early glottic cancer patients treated with transoral laser microsurgery: age, gender, stage and time dependence

Abstract: ObjectivesTransoral laser microsurgery is an increasingly common treatment modality for glottic carcinoma. This study aimed to determine the effect of age, gender, stage and time on voice-related quality of life using the Voice Handicap Index-10.MethodsPrimary early glottic carcinoma patients treated with transoral laser microsurgery were included in the study. Self-reported Voice Handicap Index testing was completed pre-operatively, three months post-operatively, and yearly at follow-up appointments.ResultsVo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…However, during the 1st year of follow‐up, patients treated with both radiotherapy modalities showed a steeper and clinically significant improvement compared to a more stable and clinically insignificant improvement over time with TLM. The nonlinear stable trajectory for TLM has been described previously by Lane et al 40 It is in accordance with the belief that full remodeling of the glottic tissue takes 12 to 24 months. However, because the first follow‐up measurement is taken at 2 to 4 months, short deteriorations after surgery may go undetected.…”
Section: Discussionsupporting
confidence: 85%
“…However, during the 1st year of follow‐up, patients treated with both radiotherapy modalities showed a steeper and clinically significant improvement compared to a more stable and clinically insignificant improvement over time with TLM. The nonlinear stable trajectory for TLM has been described previously by Lane et al 40 It is in accordance with the belief that full remodeling of the glottic tissue takes 12 to 24 months. However, because the first follow‐up measurement is taken at 2 to 4 months, short deteriorations after surgery may go undetected.…”
Section: Discussionsupporting
confidence: 85%
“…The attenuation of post-interventional dysphonia in early glottic cancer should be viewed in this context, taking into account the importance of identifying voice outcomes as a function of time on patients'quality of life. Indeed, patients and physicians should realize the non-linear course of postinterventional improvement in voice handicap, 8 and acknowledge the optimal time of voice function return, which does seem to be extending up to two years posttreatment, according to the results of the present study.…”
Section: Discussionmentioning
confidence: 60%
“…While the improvement of postoperative VHI-10 scores in patients with EGC treated with TLM is well established and seems, in fact, to be extending well into the 2 nd postoperative year, 8 meta-analyses have indicated that the perceptive and acoustic vocal quality of their radiotherapy-only counterparts may be even better. 1 9 However, by applying element analysis of the VHI-10, the present study identified that when these radical single-treatment modalities are combined, the postinterventional intelligibility of the patients' speech in noisy environments may pose as the primary parameter of voice handicap in the 2 nd postintervention year ( p = 0.000).…”
Section: Discussionmentioning
confidence: 99%
“…Lane et al . found that VHI-10 scores show maximal improvement 5.5 months after TLM [ 26 ]. Other authors argue that voice assessments should be performed at least 6–12 months post-TLM to allow post-operative edema to resolve [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, most patients in our cohort had a type IV or V cordectomy, which is associated with worse subjective voice outcomes post-operatively. Additionally, advanced age correlates with worse voice outcomes [ 26 ]. Although the average age in our cohort was 70.2 years; we found no difference in VHI-10 or MPT in patients under the age of 70 years in either group.…”
Section: Discussionmentioning
confidence: 99%